Inhibition performance of Glycine max, Cuscuta reflexa and Spirogyra extracts for mild steel dissolution in acidic medium: Density functional theory and experimental studies - D.K. Verma; Fahmida Khan; I. Bahadur; Mohammad Salman; M.A. Quraishi; Chandrabhan Verma; Eno E. Ebenso (Results in Physics, 2018)
The effectiveness of three plant extracts namely Glycine max leaves (GMLE), Cuscuta reflexa roxb. (CRRE) and Spirogyra algae (SGAE) has been evaluated as green corrosion inhibitors for mild steel corrosion in acidic solution of 1 M HCl using chemical, electrochemical, surface and density functional theory (DFT) methods. The gravimetric and electrochemical results showed that the trend of their effectiveness towards mild steel acidic corrosion inhibition follows the order: GMLE > CRRE > SGAE. Polarization study suggested that tested plant extracts acted as mixed type inhibitors with slight anodic dominance. The GMLE, CRRE and SGAE extracts showed maximum inhibition efficiencies of 73.60%, 81.92% and 94.05%, respectively at 2 g L−1 concentration. Results of gravimetric measurements showed that effectiveness of the plant extracts enhances on enhancing their concentrations. Gravimetric measurements carried out at different temperature showed that adsorption of the plant extracts mainly involve physisorption mechanism. Investigated extracts behaved as interface inhibitors and their adsorption mechanism obeyed the Langmuir adsorption isotherm. Surface morphology and elemental composition was determined to support the adsorption inhibitive mechanism. Scanning electron microscope (SEM) analyses carried out in the association with electron dispersive X-ray spectroscopy (EDS) further supported the adsorption inhibitive mechanism. Density Functional Theory (DFT) study was carried out on major phytochemicals present in the extract in order to support the experimental results and explain the adsorption behaviour of phytochemicals (extracts). Keywords: Acid solution, Electrochemical studies, Adsorption, Mild steel, Green inhibitors, EDS-SEM